Pengaruh Financial Literacy, Personal Interest, dan Environment terhadap Minat Investasi Saham Syariah pada Generasi Muda Bengkulu - Nanda Puspitasari; Herlina Yustati (At-Thariqah: Jurnal Ekonomi, 2024)
Investment is the first step in production activities and is a factor to increase economic growth, thus investment is essentially also the first step of economic development activities. Knowledge of financial management and investment has become very important in this era and should not be ignored as before. One of the components that influence investment is an increase in national income, or economic growth. Knowledge about investment aims to keep young investors in particular, away from irrational investment practices. The problem faced is that there are still many young people who do not understand about investment. This study aims to examine the interest of young investors in syariah index investing. Samples were taken from the younger generation in Bengkulu city as many as 100 samples spread across Bengkulu City. Data analysis uses quantitative analysis methods by conducting hypothesis testing on the perceptions of respondents. The results of the study have implications for increasing the number of young people who are interested in investing in shariah index in Bengkulu City. Keywords : Investment, Financial Literacy, Personal Interset, Young Investors